Comparison of three aphrodisiac plants (eurycoma longifolia, polyalthia bullata and stema tuberosa) synonymous with tongkat Ali - Fatinah, Ahmad; Sharifah Aminah, Tuan Said; Chakravarthi, Srikumar; Aini Norhidayah, Mohamed; Raihana Z.B., Edros; Jaya Vejayan, Palliah (Faculty of Pharmacy, University of Benin, 2023)
The indigenous people of Malaysia pioneered the use of Tongkat Ali for its aphrodisiac purposes. They gave at least three plants the common name of Tongkat Ali, including E. longifolia, P. bullataand S. tuberosa. Since E. longifoliais the most widely used root of the three, it has undergone extensive research compared to P. bullataand S. tuberosa. Proteins found in E. longifoliahave been proven to be the aphrodisiac bioactive constituent. Parameters such as pH level, moisture content, heavy metal content and microbial load were compared between all three roots after aqueous extraction under reflux, followed by quantitative protein assay, SDS PAGE and HPLC. The pH and moisture content of the extracts were within the acceptable ranges of 5% to 6% and 3% to 7% (w/w), respectively; additionally, no heavy metals were found. Microbes, which were initially detected, were undetectable once a decontamination step was introduced during the treatment. The protein yield for E. longifolia, P. bullataand S. tuberosawere 0.014%, 0.008% and 0.006% (w/w), respectively, and the SDS PAGE provided a single band within the range of 10 to 20 kDa molecular weight. The HPLC of Eurycomanone, a common quassinoid compound, was found in E. longifoliabut not in the other two Tongkat Ali. In conclusion, the three plants investigated possess several physicochemical differences but share the same protein, likely contributing to their aphrodisiac activity.